2021
DOI: 10.3389/fpls.2021.723363
|View full text |Cite
|
Sign up to set email alerts
|

The Major Peanut Allergen Ara h 2 Produced in Nicotiana benthamiana Contains Hydroxyprolines and Is a Viable Alternative to the E. Coli Product in Allergy Diagnosis

Abstract: Peanut allergy is a potentially life-threatening disease that is mediated by allergen-specific immunoglobulin E (IgE) antibodies. The major peanut allergen Ara h 2, a 2S albumin seed storage protein, is one of the most dangerous and potent plant allergens. Ara h 2 is posttranslationally modified to harbor four disulfide bridges and three hydroxyprolines. These hydroxyproline residues are required for optimal IgE-binding to the DPYSPOHS motifs representing an immunodominant IgE epitope. So far, recombinant Ara … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…There is quite some evidence that the proline-rich epitope on Ara h 2 between positions 40 and 70 is a dominant IgE epitope in which prolines are hydroxylated. 27 29 That stretch includes an alpha helix and a well-exposed extended loop. 30 Also in our experiments, a synthetic peptide spanning amino acids 42 to 68, with prolines in hydroxylated form, exhibited strong inhibitory potency, being able to reduce IgE binding to nAra h 2 by around 40%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is quite some evidence that the proline-rich epitope on Ara h 2 between positions 40 and 70 is a dominant IgE epitope in which prolines are hydroxylated. 27 29 That stretch includes an alpha helix and a well-exposed extended loop. 30 Also in our experiments, a synthetic peptide spanning amino acids 42 to 68, with prolines in hydroxylated form, exhibited strong inhibitory potency, being able to reduce IgE binding to nAra h 2 by around 40%.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation here is that Escherichia coli –produced rAra h 2 does not have hydroxy prolines, which have been shown to be important for IgE binding. 9 , 27 , 29 For Ara h 2, therefore, a natural purified or a plant-expressed recombinant may be preferred. Indeed, it was recently reported that a recombinant Ara h 2 molecule produced in Nicotiana benthamiana contained hydroxylated prolines and bound IgE more efficiently than recombinant Ara h 2 produced in E coli .…”
Section: Discussionmentioning
confidence: 99%
“…Excess of BDNF 2 dimers will dilute and dissolve existing TrkB 2 -BDNF 2 tetramers into TrkB 1 -BDNF 2 trimers. Such a biphasic concentration-dependent receptor dimerization is well characterized in immunology, for instance, in rat basophile release assays [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there has been considerable effort in glycoengineering popular expression hosts such as Nicotiana benthamiana , N. tabacum , tobacco BY2 cells and the moss Physcomitrella patens towards humanized- and customized N-glycosylation ( Bakker et al, 2001 ; Koprivova et al, 2004 ; Strasser et al, 2008 ; Kallolimath et al, 2016 ; Limkul et al, 2016 ; Mercx et al, 2017 ; Jansing et al, 2019 ; Bohlender et al, 2020 ; Herman et al, 2021 ; Göritzer et al, 2022 ; Kogelmann et al, 2023 ) limited attention was cast towards modulating the plant endogenous O-glycosylation pathway ( Castilho et al, 2012 ; Yang et al, 2012 ; Parsons et al, 2013 ; Dicker et al, 2016 ; Ramírez-Alanis et al, 2018 ; Mócsai et al, 2021 ; Uetz et al, 2022 ). Plant-endogenous HyP and further modifications with pentoses (arabinoses) were found in several recombinantly produced proteins such as IgA1, MUC1, EPO-Fc, and Ara h 2 ( Karnoup et al, 2005 ; Weise et al, 2007 ; Pinkhasov et al, 2011 ; Castilho et al, 2012 ; Yang et al, 2012 ; Üzülmez et al, 2021 ). The impact of these plant-specific HyP residues and attached pentoses on the function and potency of therapeutic proteins is currently unknown.…”
Section: Introductionmentioning
confidence: 99%